Lysophosphatidic Acid Signaling and microRNAs: New Roles in Various Cancers - Rafiyan, Mahdi; Abadi, Mohammad Hassan Jafari Najaf; Zadeh, Seyed Saeed Tamehri; Hamblin, Michael R.; Mousavi, Mahboubeh; Mirzaei, Hamed (Frontiers in Oncology, 2022)
A wide range of microRNAs (miRNAs) are coded for in the human genome and contribute to the regulation of gene expression. MiRNAs are able to degrade mRNAs and/or prevent the RNA transcript from being translated through complementary binding of the miRNA seed region (nucleotide 2-8) to the 3'-untranslated regions of many mRNAs. Although miRNAs are involved in almost all processes of normal human cells, they are also involved in the abnormal functions of cancer cells. MiRNAs can play dual regulatory roles in cancer, acting either as tumor suppressors or as tumor promoters, depending on the target, tumor type, and stage. In the current review, we discuss the present status of miRNA modulation in the setting of lysophosphatidic acid (LPA) signaling. LPA is produced from lysophosphatidylcholine by the enzyme autotaxin and signals via a range of G protein-coupled receptors to affect cellular processes, which ultimately causes changes in cell morphology, survival, proliferation, differentiation, migration, and adhesion. Several studies have identified miRNAs that are over-expressed in response to stimulation by LPA, but their functional roles have not yet been fully clarified. Since RNA-based treatments hold tremendous promise in the area of personalized medicne, many efforts have been made to bring miRNAs into clinical trials, and this field is evolving at an increasing pace.